Heterosexual Transmission of Human Immunodeficiency Virus Type 1 Subtype C: Macrophage Tropism, Alternative Coreceptor Use, and the Molecular Anatomy of CCR5 Utilization - Isaacman-Beck, Jesse (American Society for Microbiology (ASM), 2009)
Human immunodeficiency virus type 1 transmission selects for virus variants with genetic characteristics distinct from those of donor quasispecies, but the biological factors favoring their transmission or establishment in new hosts are poorly understood. We compared primary target cell tropisms and entry coreceptor utilizations of donor and recipient subtype C Envs obtained near the time of acute infection from Zambian heterosexual transmission pairs. Both donor and recipient Envs demonstrated only modest macrophage tropism, and there was no overall difference between groups in macrophage or CD4 T-cell infection efficiency. Several individual pairs showed donor/recipient differences in primary cell infection, but these were not consistent between pairs. Envs had surprisingly broad uses of GPR15, CXCR6, and APJ, but little or no use of CCR2b, CCR3, CCR8, GPR1, and CXCR4. Donors overall used GPR15 better than did recipients. However, while several individual pairs showed donor/recipient differences for GPR15 and/or other coreceptors, the direction of the differences was inconsistent, and several pairs had unique alternative coreceptor patterns that were conserved across the transmission barrier. CCR5/CCR2b chimeras revealed that recipients as a group were more sensitive than were donors to replacement of the CCR5 extracellular loops with corresponding regions of CCR2b, but significant differences in this direction were not consistent within pairs. These data show that sexual transmission does not select for enhanced macrophage tropism, nor for preferential use of any alternative coreceptor. Recipient Envs are somewhat more constrained than are donors in flexibility of CCR5 use, but this pattern is not universal for all pairs, indicating that it is not an absolute requirement.